Multiple Intelligences-Based Learning Guidance at SMAN 1 Garut - Rahadian, Dian; Nurhayadi, Adi; Rahayu, Irawati (Fakultas Kewirausahaan Universitas Garut, 2024)
This community service program aims to enhance the quality of learning at SMAN 1 Garut through the implementation of Multiple Intelligences (MI)-based learning guidance. The activity involved three stages: introducing the concept of MI to students, explaining its integration into classroom practices, and applying MI-based learning strategies in real sessions. The guidance was designed to accommodate students’ diverse intelligence profiles, promoting personalized learning experiences. The results show that MI-based learning creates a more engaging and inclusive classroom environment, enabling students to develop cognitive, social, and emotional competencies. This approach not only improves academic achievement but also strengthens students’ confidence, creativity, and collaboration skills, which are essential in the digital era. The program demonstrates that applying MI principles can optimize students’ potential holistically and serves as a practical model for innovative teaching strategies in senior high schools.